Association of Chronic Obstructive Pulmonary Disease With Arrhythmia Risks: A Systematic Review and Meta-Analysis - Liu, Xin; Chen, Zhuohui; Li, Siyuan; Xu, Shuo (Frontiers in Cardiovascular Medicine, 2021)
Abstract Background: A large number of studies have shown that the common causes of death are cardiovascular events among chronic obstructive pulmonary disease (COPD) patients, and several evidences suggest that some potential causes may be partly due to arrhythmia risks. However, the association of COPD with risks of arrhythmias has never been systematically reviewed. Therefore, we performed the meta-analysis with the aim of articulating the relationship between COPD and arrhythmia risks. Methods: A systematic retrieval was carried out within the databases of Web of Science, Embase, PubMed and the Cochrane Library. The random-effects model was used to pool studies due to the potential heterogeneity across the included studies. In the sensitivity analysis, we re-performed the analysis using the fixed-effects model the risk ratios (RRs) with 95% confidence intervals (CIs) were regarded as effect estimates. Results: A total of 21 studies were included in our current meta-analysis. In the pooled analysis by the random-effects model, the results showed that COPD was significantly related with the risk of atrial fibrillation (RR=1.99, 95% CI: 1.46-2.70), ventricular arrhythmias (RR=2.01, 95% CI: 1.42-2.85) and sudden cardiac death (RR=1.68, 95% CI: 1.28-2.21). In the sensitivity analysis, the pooled results were stable when we re-performed the above-mentioned analysis using the fixed-effects model. In addition, the corresponding results were not changed after exclusion one study at a time. Conclusions: Our current data support that COPD has a positive relationship with arrhythmia risks. Further study could confirm our findings.